2022
DOI: 10.3390/inorganics10090143
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Microstructural Characterization and Photocatalysis Tests of V5+-Doped TiO2/WO3 Nanocomposites Supported on Electrospun Membranes

Abstract: Metal oxide nanocomposites (MON) have gained significant attention in the literature for the possibility of improving the optical and electronic properties of the hybrid material, compared to its pristine constituent oxides. These superior properties have been observed for TiO2 — based MON, which exhibit improved structural stability and photoactivity in environmental decontamination processes. In addition, the use of polymer membrane-supported MON is preferable to prevent further aggregation of particles, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…An illustrative diagram of this process is represented in Figure 2. The combined action of direct redox processes, induced by holes and photogenerated electrons on the surface of the catalysts, and of indirect redox processes, derived from reactive oxygen species, is responsible for pollutant degradation [13,42,43].…”
Section: Metal Oxide-based Photocatalysismentioning
confidence: 99%
See 3 more Smart Citations
“…An illustrative diagram of this process is represented in Figure 2. The combined action of direct redox processes, induced by holes and photogenerated electrons on the surface of the catalysts, and of indirect redox processes, derived from reactive oxygen species, is responsible for pollutant degradation [13,42,43].…”
Section: Metal Oxide-based Photocatalysismentioning
confidence: 99%
“…Several researchers have focused their work on the synthesis of narrow-band photocatalysts, which can be used under visible light irradiation. Various surface enhancement methods to achieve this include doping with The combined action of direct redox processes, induced by holes and photogenerated electrons on the surface of the catalysts, and of indirect redox processes, derived from reactive oxygen species, is responsible for pollutant degradation [13,42,43].…”
Section: Metal Oxide-based Photocatalysismentioning
confidence: 99%
See 2 more Smart Citations
“…Pereira et al [16] reported the preparation of V-doped titania/WO 3 (1:1 molar ratio) nanocomposites with different dopant concentrations and dispersed them in high-surfacearea fibrous polymeric membranes obtained by means of electrospinning deposition. Evidence demonstrated that: (i) V 5+ ions doped the atomic structure of titania (anatase phase), (ii) the titania crystallite sizes slightly increased by increasing the dopant concentration, and (iii) both W 6+ and V 5+ occupies Ti 4+ vacancies in the anatase crystal lattice, allowing for a greater degree of local vibrations, which favors the occurrence of photocatalytic processes.…”
mentioning
confidence: 99%